Ceramic tile with jade fat skin effect and preparation method thereof
High thermal conductivity and machinery of ceramic tile are solved by using microporous calcium silicate and potassium hexatitinolate whiskers in ceramic tile and using specific materials and firing systems in the glaze layer to form the appropriate gloss and touch. The problem of insufficient strength has achieved low thermal conductivity, high strength and jade fat skin effect.
Patent Information
- Application Number
- CN202411702480.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
The existing skin glaze ceramic tiles have high thermal conductivity, cool touch, and low mechanical strength. The glaze is not delicate and warm enough, which cannot achieve the soft luster like jade and the skin-friendly effect of tentacles.
Using a ceramic tile structure that includes the lower body layer, the upper body layer, the jade fat skin glaze layer and the matte transparent protective glaze layer from bottom to top, microporous calcium silicate and potassium hexatolitic acid are added to the upper body layer. Whiskers are used to isolate the coolness of ceramic tiles, and use high bauxite, calcium feldspar, calcite, chestnut ash and other materials in the glaze layer of jade fat skin. Spherical droplets and microcrystals are formed through the firing system to produce spherical droplets and microcrystals. Promotes scattering, achieving a soft luster and warm effect.
It achieves the low thermal conductivity, high mechanical strength, and the glaze effect of jade fat skin, making the surface of the ceramic tiles warm and skin-friendly feel, and has a soft luster like jade.
Smart Images

Figure CN119462109A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building ceramics, and in particular relates to a ceramic tile with a jade-like skin effect and a preparation method thereof. Background Art
[0002] The ceramic industry has always been dominated by glossy bricks, which are high-end, easy to clean and maintain, and neat in style. However, with the development of the times, consumer demands are becoming more and more diversified. Compared with the bright and eye-catching and colorful glossy bricks, simple and pure tones and quiet and comfortable, warm and soft skin glaze products are like a clear stream away from the hustle and bustle of the city, becoming the pursuit and choice of more and more people.
[0003] At present, most of the skin-glazed ceramic tiles on the market, although they can achieve a soft light effect (glossiness between 15-25°), have high thermal conductivity like most ceramic materials. When in contact with air, they will quickly adjust their own temperature to the temperature of the surrounding environment. Therefore, especially when the temperature is low, the surface temperature of ceramic tiles is lower than that of other materials such as wood or fabric. And because of the good thermal conductivity of ceramic tiles, they are also very sensitive to temperature changes. When the outside temperature drops, the temperature of the ceramic tiles will drop rapidly, so when you touch it, you will feel cold, and it does not have the skin-friendly touch of warm touch. In addition, the mechanical strength of existing skin-glazed ceramic tiles is generally not high, and the glaze surface is not delicate enough, and the light transmittance is poor; it is impossible to achieve a soft and warm visual effect like jade.
[0004] Therefore, there is an urgent need to develop a high-strength ceramic glazed tile that has a skin-friendly touch and is warm to the touch, and the glaze is delicate and warm, with a soft jade-like luster, achieving a jade-like skin effect. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a ceramic tile with a jade-like glaze effect and a preparation method thereof, wherein the ceramic tile has a low thermal conductivity, high mechanical strength, and a jade-like glaze effect.
[0006] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic tile, which includes, from bottom to top, a lower body layer, an upper body layer, a jade-skin-like glaze layer and a matte transparent protective glaze layer, and the raw materials for preparing the upper body layer contain microporous calcium silicate and potassium hexatitanate whiskers.
[0007] Specifically, the present invention sets two layers of green body and adds a certain amount of microporous calcium silicate and potassium hexatitanate whiskers in the upper green body layer to isolate the coolness of the ceramic tile green body, so that the surface of the ceramic tile has a skin-friendly effect of being warm to the touch, and improves the mechanical strength of the green body. Among them: microporous calcium silicate is a silicate material with light bulk density and low thermal conductivity. It can not only effectively inhibit solid-state heat conduction and gas convection heat transfer, effectively isolate the coolness of the ceramic tile green body, and reduce the conduction of heat, so that the ceramic tile has a warm touch; and calcium silicate itself is also a ceramic green body raw material. After high-temperature firing, it can react with other ceramic raw materials to precipitate calcium feldspar crystals. Potassium hexatitanate whiskers have high infrared reflection performance, low thermal conductivity, and excellent thermal insulation performance. They can work together with microporous calcium silicate to isolate the coolness of ceramic tile bodies. At the same time, potassium hexatitanate whiskers are also good ceramic reinforcement materials. After being compounded with microporous calcium silicate, they will fill the gaps in the micropores, which will further reduce the thermal conductivity of ceramic tiles while also helping to improve the mechanical strength of the bricks.
[0008] In some embodiments of the present invention, the raw materials for preparing the upper body layer further include a basic blank, and the chemical composition of the basic blank includes, by weight percentage: SiO 2 62-68%, Al 2 O 3 15-25%, Fe 2 O 3 0.3-0.5%, TiO 2 0.2-0.4%, CaO 1-3%, MgO 1-3%, K 2 O 2-5%, Na 2 O 2-5%, loss on ignition 2-4%.
[0009] In some embodiments of the present invention, the chemical composition of the lower body layer is the same as the chemical composition of the base body. The lower body layer is prepared using raw materials with the same chemical composition as the base body of the upper body layer, which is beneficial to increase the compatibility inside the body, reduce the defects of interlayer cracking or delamination, and thus ensure the mechanical strength of the body.
[0010] In some embodiments of the present invention, in the raw materials for preparing the upper green body layer, the content of the microporous calcium silicate is 5-10wt%, and the content of the potassium hexatitanate whisker is 5-10wt%. Controlling the amount of microporous calcium silicate and potassium hexatitanate whisker added can reduce the thermal conductivity of the green brick while improving the mechanical strength of the product.
[0011] In some embodiments of the present invention, the aspect ratio of the potassium hexatitanate whiskers is 20-40.
[0012] In some embodiments of the present invention, the thickness ratio of the upper body layer to the lower body layer is (1-3):(7-9).
[0013] In some embodiments of the present invention, the raw material components of the jade skin glaze layer include, by weight: 40-55 parts of high alumina, 15-25 parts of calcium feldspar, 10-20 parts of chestnut ash, 8-15 parts of calcite, 1-3 parts of animal bone meal, 3-5 parts of agate powder, and 0.5-1 part of colorant; the colorant includes golden clay or vanadium pentoxide.
[0014] Specifically, the jade skin glaze layer of the present invention uses high alumina (clay with an aluminum content of more than 50wt%), calcium feldspar, calcite and chestnut ash as main raw materials, and adds a certain amount of animal bone powder, agate powder and colorant to achieve the glaze's gloss and soft effect like jade. 2 O 3 In this system, it is more conducive to the precipitation of mullite and magnesium aluminum spinel, and improves the mechanical properties of the glaze. 2 CO 3 , and contains a small amount of elements such as Ca, Mg, K + As a network modifier, it balances the charge and is beneficial to the phase separation of glaze melt. The main component of animal bone powder is Ca 3 (PO 4 ) 2 , P 2 O 5 As a glass phase former, SiO 2 The ion field strength is different, and P 5+ The attraction to oxygen atoms is greater than that to Si 4+ , so P 5+ It is easier to capture CaO, MgO and K in the glaze melt 2 O's oxygen atoms are added to obtain the best coordination number to form a phosphorus-oxygen polymer, thereby forming a phase separation structure. At the same time, the phase separation structure is beneficial to further promote the precipitation of crystals such as mullite, calcium feldspar and magnesium aluminum spinel in the glaze layer. The present invention controls the dosage relationship of each raw material and the firing system, so that a certain amount of spherical droplets and microcrystals are distributed in the glaze melt at the same time, and their size is close to the wavelength of visible light, resulting in Rayleigh scattering, so that the glaze surface produces a jade-like soft effect. In addition, agate powder is translucent and has a jade-like luster, which is beneficial to further enhance the jade-like skin effect of the glaze surface; golden soil and vanadium pentoxide are colorants, which are gray and light yellow respectively under a reducing atmosphere.
[0015] In some embodiments of the present invention, the thickness of the jade-fat skin glaze layer is 0.3-0.5 mm. Properly increasing the thickness of the jade-fat skin glaze layer is more conducive to the presentation of the glazed jade-fat skin effect.
[0016] In some embodiments of the present invention, the raw material components of the matte transparent protective glaze layer include, by weight: 25-35 parts of feldspar, 20-30 parts of clay, 15-20 parts of quartz, 10-15 parts of barium carbonate, 8-15 parts of calcium carbonate, 5-10 parts of kaolin, 2-5 parts of titanium dioxide, 1-3 parts of zirconium silicate, and 2-6 parts of limestone. The matte transparent protective glaze layer is mainly used to adjust the glossiness of the glaze surface to achieve a soft light effect.
[0017] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic tile, comprising the following steps:
[0018] (1) respectively taking raw materials for preparing the lower green body layer and the upper green body layer, preparing them into powder, distributing them in sequence, forming them, and drying them to obtain the lower green body layer and the upper green body layer;
[0019] (2) applying a top glaze and a protective glaze in sequence on the surface of the upper body layer to form a jade-like top glaze layer and a matte transparent protective glaze layer; and drying and firing to obtain the ceramic tile.
[0020] In some embodiments of the present invention, in step (2), the sintering atmosphere is a reducing atmosphere.
[0021] Specifically, sintering under a reducing atmosphere is more conducive to the coloring of golden clay and vanadium pentoxide, wherein golden clay is gray when sintered under a reducing atmosphere, and vanadium pentoxide is light yellow when sintered under a reducing atmosphere.
[0022] In some embodiments of the present invention, in step (2), the maximum sintering temperature is 1150-1230°C.
[0023] In some embodiments of the present invention, in step (2), the firing temperature regime is: firstly increase the temperature to 800-900°C at a heating rate of 15-20°C / min, and keep it at that temperature for 10-15min; then increase the temperature to 1150-1230°C at a heating rate of 8-10°C / min, keep it at that temperature for 15-20min, and finally cool naturally after leaving the kiln.
[0024] Specifically, during the heating process, the present invention first heats up to 800-900°C at a faster rate and keeps the temperature for a certain period of time; then heats up to the highest temperature at a slower rate to control the size of the phase separation droplets and promote the precipitation and growth of crystals, thereby obtaining the best jade-like skin effect.
[0025] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0026] The ceramic tile of the present invention includes, from bottom to top, a lower body layer, an upper body layer, a jade-like skin glaze layer and a matte transparent protective glaze layer, wherein: microporous calcium silicate and potassium hexatitanate whiskers are added to the upper body layer at the same time, and the two raw materials interact with each other to isolate the coolness of the ceramic tile body, so that the surface of the ceramic tile has a skin-friendly effect of being warm to the touch, and the mechanical strength of the brick body is improved. The jade-like skin glaze layer uses high alumina, calcium feldspar, calcite and chestnut ash as main raw materials, and by adding a certain amount of animal bone powder, agate powder and colorant, and controlling the dosage relationship and firing system of each raw material, a certain amount of spherical droplets and microcrystals are distributed in the glaze melt at the same time, and their size is close to the wavelength of visible light, resulting in Rayleigh scattering, so that the glaze surface has a jade-like soft effect. The matte transparent protective glaze layer is mainly used to adjust the glossiness of the glaze surface within the soft light range of 15-25°. The body layer, the jade-like glaze layer and the matte transparent protective glaze layer work together and cooperate with each other to achieve the low thermal conductivity, high mechanical strength and jade-like glaze effect of the ceramic tile. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of the glaze surface of the ceramic tile prepared in Example 1;
[0028] Figure 2 This is a real picture of the glaze surface of the ceramic tile prepared in Example 2. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0030] Example 1
[0031] A ceramic tile comprises, from bottom to top, a lower body layer, an upper body layer, a jade-skin surface glaze layer and a matte transparent protective glaze layer.
[0032] The raw material components of the upper body layer are as follows by weight: 85% of basic body, 5% of microporous calcium silicate and 10% of potassium hexatitanate whiskers.
[0033] The chemical composition of the base blank, by weight percentage, includes: SiO 2 65%,Al 2 O 3 20%,Fe 2O 3 0.3%, TiO 2 0.2%, CaO 2%, MgO 2%, K 2 O 4%, Na 2 O 3%, ignition loss 3.5%; the aspect ratio of potassium titanate whiskers is 30.
[0034] The chemical composition of the lower body layer is the same as that of the base body, and the thickness ratio of the upper body layer to the lower body layer is 2:8.
[0035] The raw material components of the jade skin glaze layer include, by weight: 45.4 parts of high alumina, 20.4 parts of calcium feldspar, 17.2 parts of chestnut ash, 11 parts of calcite, 2 parts of animal bone powder, 3.5 parts of agate powder, and 0.5 parts of golden soil. The thickness of the jade skin glaze layer is 0.3 mm.
[0036] The raw material components of the matte transparent protective glaze layer include, by weight: 27 parts of feldspar, 20 parts of clay, 18 parts of quartz, 12 parts of barium carbonate, 8 parts of calcium carbonate, 6 parts of kaolin, 3 parts of titanium dioxide, 3 parts of zirconium silicate, and 4 parts of limestone.
[0037] The method for preparing the ceramic tile comprises the following steps:
[0038] (1) taking the raw materials for preparing the lower green body layer and the upper green body layer respectively, preparing the powders, distributing the powders in sequence, pressing and forming the powders with a 4000-ton press, and drying the powders to obtain the lower green body layer and the upper green body layer;
[0039] (2) The raw materials of the jade-like skin glaze layer and the matte transparent protective glaze layer are mixed, wet ball milled, iron removed and homogenized to obtain the surface glaze slurry and the protective glaze slurry, which are then sprayed on the surface of the upper body layer in turn, and fired in a kiln under a reducing atmosphere to obtain the ceramic tile of this embodiment. The firing temperature system is: first, the temperature is raised to 850°C at a heating rate of 15°C / min, and the temperature is kept for 15 minutes; then, the temperature is raised to 1200°C at a heating rate of 10°C / min, and the temperature is kept for 15 minutes, and finally, the ceramic tile is taken out of the kiln and cooled naturally.
[0040] Example 2
[0041] A ceramic tile comprises, from bottom to top, a lower body layer, an upper body layer, a jade-skin surface glaze layer and a matte transparent protective glaze layer.
[0042] The raw material components of the upper green body layer are as follows by weight percentage: 90% of basic green body, 5% of microporous calcium silicate and 5% of potassium hexatitanate whiskers.
[0043] The chemical composition of the base blank, by weight percentage, includes: SiO 2 65%,Al 2 O 320%,Fe 2 O 3 0.3%, TiO 2 0.2%, CaO 2%, MgO 2%, K 2 O 4%, Na 2 O 3%, ignition loss 3.5%; the aspect ratio of potassium titanate whiskers is 20.
[0044] The chemical composition of the lower body layer is the same as that of the base body, and the thickness ratio of the upper body layer to the lower body layer is 2:8.
[0045] The raw material components of the jade-fat skin glaze layer include, by weight: 48.4 parts of high alumina, 17.5 parts of calcium feldspar, 16.6 parts of chestnut ash, 10 parts of calcite, 3 parts of animal bone powder, 3.5 parts of agate powder, and 1 part of vanadium pentoxide. The thickness of the jade-fat skin glaze layer is 0.3 mm.
[0046] The raw material components of the matte transparent protective glaze layer include, by weight: 30 parts of feldspar, 20 parts of clay, 15 parts of quartz, 10 parts of barium carbonate, 10 parts of calcium carbonate, 8 parts of kaolin, 3 parts of titanium dioxide, 2 parts of zirconium silicate, and 2 parts of limestone.
[0047] The method for preparing the ceramic tile comprises the following steps:
[0048] (1) taking the raw materials for preparing the lower green body layer and the upper green body layer respectively, preparing the powders, distributing the powders in sequence, pressing and forming the powders with a 3000-ton press, and drying the powders to obtain the lower green body layer and the upper green body layer;
[0049] (2) The raw materials of the jade-like skin glaze layer and the matte transparent protective glaze layer are mixed, wet ball milled, iron removed and homogenized to obtain the surface glaze slurry and the protective glaze slurry, which are then sprayed on the surface of the upper body layer in turn, and fired in a kiln under a reducing atmosphere to obtain the ceramic tile of this embodiment. The firing temperature system is: first, the temperature is raised to 800°C at a heating rate of 18°C / min, and the temperature is kept for 15 minutes; then, the temperature is raised to 1150°C at a heating rate of 10°C / min, and the temperature is kept for 20 minutes, and finally, the ceramic tile is taken out of the kiln and cooled naturally.
[0050] Example 3
[0051] A ceramic tile comprises, from bottom to top, a lower body layer, an upper body layer, a jade-skin surface glaze layer and a matte transparent protective glaze layer.
[0052] The raw material components of the upper body layer are as follows by weight: 85% of basic body, 5% of microporous calcium silicate and 10% of potassium hexatitanate whiskers.
[0053] The chemical composition of the base blank, by weight percentage, includes: SiO 2 65%,Al2 O 3 20%,Fe 2 O 3 0.3%, TiO 2 0.2%, CaO 2%, MgO 2%, K 2 O 4%, Na 2 O 3%, ignition loss 3.5%; the aspect ratio of potassium titanate whiskers is 30.
[0054] The chemical composition of the lower body layer is the same as that of the base body, and the thickness ratio of the upper body layer to the lower body layer is 2:8.
[0055] The raw material components of the jade skin glaze layer include, by weight: 51.6 parts of high alumina, 20.1 parts of calcium feldspar, 11.3 parts of chestnut ash, 8 parts of calcite, 3 parts of animal bone powder, 4.5 parts of agate powder, and 0.8 parts of golden soil. The thickness of the jade skin glaze layer is 0.4 mm.
[0056] The raw material components of the matte transparent protective glaze layer include, by weight: 28 parts of feldspar, 22 parts of clay, 15 parts of quartz, 10 parts of barium carbonate, 8 parts of calcium carbonate, 8 parts of kaolin, 4 parts of titanium dioxide, 3 parts of zirconium silicate, and 2 parts of limestone.
[0057] The method for preparing the ceramic tile comprises the following steps:
[0058] (1) taking the raw materials for preparing the lower green body layer and the upper green body layer respectively, preparing the powders, distributing the materials in sequence, pressing and molding them with a 5000-ton press, and drying them to obtain the lower green body layer and the upper green body layer;
[0059] (2) The raw materials of the jade-like skin glaze layer and the matte transparent protective glaze layer are mixed, wet ball milled, iron removed and homogenized to obtain the surface glaze slurry and the protective glaze slurry, which are then sprayed on the surface of the upper body layer in turn, and fired in a kiln under a reducing atmosphere to obtain the ceramic tile of this embodiment. The firing temperature system is: first, the temperature is raised to 800°C at a heating rate of 20°C / min, and the temperature is kept for 10 minutes; then, the temperature is raised to 1230°C at a heating rate of 8°C / min, and the temperature is kept for 15 minutes, and finally, the ceramic tile is taken out of the kiln and cooled naturally.
[0060] Comparative Example 1
[0061] The difference between Comparative Example 1 and Example 1 is that, in the raw material components of the upper body layer of Comparative Example 1, an equal amount of aluminum oxide whiskers is used to replace the potassium hexatitanate whiskers of Example 1.
[0062] Comparative Example 2
[0063] The difference between Comparative Example 2 and Example 1 is that, in the raw material components of the upper green body layer of Comparative Example 2, an equal amount of glass microspheres is used to replace the microporous calcium silicate in Example 1.
[0064] Comparative Example 3
[0065] The only difference between Comparative Example 3 and Example 1 is that the jade skin glaze layer component of Comparative Example 3 does not contain agate powder.
[0066] Comparative Example 4
[0067] The only difference between Comparative Example 4 and Example 1 is that the jade skin glaze layer of Comparative Example 4 adopts ordinary transparent glaze, and its raw material components, by weight, include: 30 parts of potassium feldspar, 7 parts of dolomite, 10 parts of burned talc, 6 parts of diopside, 4 parts of wollastonite, 6 parts of barium sulfate, 6 parts of zinc oxide, 15 parts of quartz, 5 parts of kaolin, 4 parts of corundum, 5 parts of transparent frit, and 2 parts of calcium carbonate.
[0068] Comparative Example 5
[0069] The only difference between Comparative Example 5 and Example 1 is that, during the preparation of the ceramic tile of Comparative Example 5, the firing temperature regime is: firstly, the temperature is raised to 1200°C at a heating rate of 15°C / min, and kept at that temperature for 30 minutes; then, the ceramic tile is taken out of the kiln and cooled naturally.
[0070] Performance Testing
[0071] The ceramic tile samples prepared in the above Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests, and their glaze quality was observed and the touch of the surface was recorded. Among them: the thermal conductivity of the ceramic tile was tested using a thermal conductivity tester (model: GA); the modulus of rupture was measured according to GBT3810.4-2016 "Ceramic Tile Test Method Part 4: Determination of Modulus of Rupture and Destructive Strength". The results are shown in Table 1.
[0072] Table 1:
[0073]
[0074] As shown in Table 1, the glossiness of the ceramic tiles prepared in Examples 1-3 is 16-23°, with a soft gloss, a delicate and moist glaze, and a soft gloss like jade. Figure 1-2 As shown; it has high mechanical strength, with a modulus of rupture of 45-47Mpa; and thermal conductivity as low as 0.081-0.093W / m·K, and the glaze has a skin-friendly touch that feels warm to the touch.
[0075] Relative to Example 1, in the raw material components of the upper body layer of Example 1, an equal amount of alumina whiskers are used to replace the potassium hexatitanate whiskers of Example 1. Due to the higher thermal conductivity of alumina whiskers, the thermal conductivity of the brick body is significantly increased, the glaze feels cold, and the mechanical strength is also reduced.
[0076] Compared with Example 1, in the raw material components of the upper green body layer of Comparative Example 2, an equal amount of glass microspheres are used to replace the microporous calcium silicate of Example 1. Although the glass microspheres have a lower thermal conductivity, due to their lower strength, some of the glass microspheres are easily broken during the green body pressing process, which greatly reduces the reduction in the thermal conductivity of the brick body. Therefore, the thermal conductivity of the ceramic brick prepared in Comparative Example 2 is significantly higher than that of Example 1, and the modulus of rupture is also reduced accordingly.
[0077] Compared with Example 1, the jade skin glaze layer component of Comparative Example 3 does not contain agate powder, resulting in poor transparency of the glaze surface, lack of the soft luster of jade, and a slight decrease in the modulus of rupture.
[0078] Compared with Example 1, the jade-like glaze layer of Comparative Example 4 adopts ordinary transparent glaze, and the ceramic tiles prepared have higher gloss, do not have the soft luster of jade, and the modulus of rupture is also lower than that of Example 1.
[0079] Compared with Example 1, the ceramic tiles of Comparative Example 5 adopt a natural cooling system during preparation. The phase-separated droplets of the required size are not formed in the jade-like glaze layer in time, which affects the precipitation and growth of crystals in the glaze layer, resulting in a rough glaze surface without the soft luster of jade, and the modulus of rupture is also reduced.
[0080] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A ceramic tile, characterized in that: From bottom to top, it includes a lower body layer, an upper body layer, a jade-skin-like glaze layer and a matte transparent protective glaze layer. The raw materials for preparing the upper body layer contain microporous calcium silicate and potassium hexatitanate whiskers.
2. The ceramic tile according to claim 1, characterized in that: The raw materials for preparing the upper body layer also contain a basic blank, and the chemical composition of the basic blank includes, by weight percentage: SiO2 62-68%, Al2O3 15-25%, Fe2O30.3-0.5%, TiO2 0.2-0.4%, CaO 1-3%, MgO 1-3%, K2O 2-5%, Na2O 2-5%, and ignition loss 2-4%; And / or, the chemical composition of the lower body layer is the same as the chemical composition of the base blank.
3. The ceramic tile according to claim 1, characterized in that: In the raw materials for preparing the upper green body layer, the content of the microporous calcium silicate is 5-10wt%, and the content of the potassium hexatitanate whiskers is 5-10wt%.
4. The ceramic tile according to claim 1 or 3, characterized in that: The aspect ratio of the potassium hexatitanate whisker is 20-40.
5. The ceramic tile according to claim 1, characterized in that: The thickness ratio of the upper body layer to the lower body layer is (1-3):(7-9).
6. The ceramic tile according to claim 1, characterized in that: The raw material components of the jade skin glaze layer include, by weight: 40-55 parts of high alumina, 15-25 parts of calcium feldspar, 10-20 parts of chestnut ash, 8-15 parts of calcite, 1-3 parts of animal bone meal, 3-5 parts of agate powder, and 0.5-1 part of colorant; the colorant includes golden clay or vanadium pentoxide.
7. The ceramic tile according to claim 1 or 6, characterized in that: The thickness of the jade skin glaze layer is 0.3-0.5mm.
8. The ceramic tile according to claim 1, characterized in that: The raw material components of the matte transparent protective glaze layer include, by weight: 25-35 parts of feldspar, 20-30 parts of clay, 15-20 parts of quartz, 10-15 parts of barium carbonate, 8-15 parts of calcium carbonate, 5-10 parts of kaolin, 2-5 parts of titanium dioxide, 1-3 parts of zirconium silicate, and 2-6 parts of limestone.
9. A method for preparing a ceramic tile according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) taking the raw materials for preparing the green body layer and the upper green body layer respectively, making them into powder, and then distributing them in sequence; After forming and drying, a lower green body layer and an upper green body layer are obtained; (2) Applying jade-like skin glaze and matte transparent protective glaze in sequence on the surface of the upper body layer to form a jade-like skin glaze layer and a matte transparent protective glaze layer; drying and firing to obtain the ceramic tile.
10. The method for preparing a ceramic tile according to claim 9, characterized in that: In step (2), the sintering atmosphere is a reducing atmosphere; and / or the maximum sintering temperature is 1150-1230°C.